Making A Movie or Making A Difference? To What Extent Do Critical Movies and Documentaries Targeting Corporations' Wrongdoing Actually Influence Their CSR Strategies? - Verre, Anna Rita (2008)
Supersize Me (2004) is a documentary whic3h highly criticizes and blames McDonald's for the spread of obesity in the US. Using a case study Supersize Me / McDonald's I will try to understand if the documentary has had some influence on McDonald's CSR (Corporate Social Responsibility) strategies. I will also try to understand if the change, if any, in the firm's CSR strategies, has been a temporary response or a permanent change. To build a theoretical framework on which I can base my following research questions I will explore the main non-market theories linked to the concept of non-market such as: CSR as a framework to manage the non-market, and the role of media within the non-market. Media have become multi-dimensional and all hyper-linked with each other. It would be useless to analyze a single medium (in this case the documentary) to show its effects on the firm's CSR strategies. That is why, to understand these effects I will first explore the impact this documentary had on other media. I will try to understand if new and general media contributed in the same way to the debate surrounding the movie. I will analyze, in a discursive way, the debate that the documentary has inspired and how this debate has shaped the public perception of the corporation. I will try to understand if the CSR framework helped the company to manage the debate. Also I will try to understand if the movie and the debate around the movie inspired some kind of organizational learning and how this process took place within the firm. This case study highlighted how critical documentaries indirectly affect the firm's CSR strategies. In fact, the large debate in the media (especially in the new media) largely influenced customer perception of the firm. This loss of legitimacy obliged the firm to start a process of learning and a debate with its stakeholders to implement new and more consistent CSR strategies.